Game and Fish Laws of the State of Delaware 16 (1927) - (:unkn) unknown (My University, 1927)
§ 2381A. Sec. 24A: Prohibited the use of any silencer or noise-reducing contrivance on any gun, rifle, or firearm when hunting game or fowl. Violators fined twenty dollars for each offense.
Keywords: HUNTING REGULATION; SUPPRESSORS